Responses of streambed bacterial groups to cycles of low‐flow and erosive floods in a small peri‐urban stream. Issue 4 (20th March 2020) - Navratil, O.; Boukerb, M.A.; Perret, F.; Breil, P.; Caurel, C.; Schmitt, L.; Lejot, J.; Petit, S.; Marjolet, L.; Cournoyer, B.
Abstract: Faecal indicator bacteria (FIB) and bacterial pathogens from combined sewer overflow (CSO) in peri‐urban streams represent a major public health concern worldwide. In this study, the relationships between the hydrological regime and the loads and persistence of CSO‐borne bacterial contaminants among benthic sediments of a small peri‐urban stream were explored. Combined sewer overflow events and their impact on benthic sediment layers at a short distance from a CSO were monitored. Concentrations of Escherichia coli (EC) and intestinal enterococci (IE) and of two bacterial pathogens, Pseudomonas aeruginosa (PA) and Aeromonas caviae (AC), were assessed. Relations with hydraulic, hydromorphic and physicochemical factors were analysed. PA cells in benthic sediments increased exponentially with time (0.15 log PA per day), as long as the river discharge remained below the sediment transport. Cycles of erosive floods and low‐flow periods were found to play a critical role in PA settling and growth among benthic riverbed sediments. These hydrological and hydraulic shear forces did not correlate with changing IE, EC, and AC concentrations in the benthic sediments. Their dynamics were rather related to changing physicochemical conditions (total N, phosphate, and organic carbon). AC population size decreases most rapidly with a mean rate of 0.04 log per day according to the duration of the low‐flow period, indicating a poor tropism of AC for river systems. River sediments were found significant biotopes for PA outdoor development. These analyses demonstrate the significance of PA and AC as long‐ and short‐term indicators, respectively, of a river microbiological quality.